Echinocandins versus non-echinocandins for empirical antifungal therapy in patients with hematological disease with febrile neutropenia: A systematic review and meta-analysis. Issue 6 (June 2020) - Yamashita, Chizuru; Takesue, Yoshio; Matsumoto, Kazuaki; Ikegame, Kazuhiro; Enoki, Yuki; Uchino, Motoi; Miyazaki, Taiga; Izumikawa, Koichi; Takada, Tohru; Okinaka, Keiji; Ueda, Takashi; Miyazaki, Yoshitsugu; et al.
Abstract: Empirical antifungal therapy is recommended in high-risk patients who have persistent febrile neutropenia (FN) despite broad-spectrum antibiotic therapy. Based on high-quality evidence, most guidelines recommend caspofungin. The aim of this study was to clarify whether echinocandins, including micafungin, are associated with improved clinical outcomes in patients with persistent FN. We conducted a meta-analysis of randomized controlled trials (RCTs) of empirical therapy with echinocandins and non-echinocandins for FN in patients with hematological disease. The primary outcome was all-cause mortality within 7 days after completion of therapy. Secondary outcomes included treatment success, and discontinuation of therapy because of adverse events. For subgroup analysis, we compared RCTs of echinocandins with liposomal amphotericin B. Six RCTs (four that evaluated caspofungin and two that evaluated micafungin) were included in the meta-analysis. Mortality and adverse events in echinocandin-treated patients were significantly lower than in those treated with non-echinocandins [risk ratio (RR) 0.70, 95% confidence interval (CI) 0.49–0.99; RR 0.48, 95% CI 0.33–0.71, respectively]. There was no significant difference in treatment success (RR 1.09, 95% CI 0.87–1.36). Mortality and adverse events in echinocandin-treated patients were significantly lower than in those treated with liposomal amphotericin B (RR 0.68, 95% CI 0.46–0.99; RR 0.53, 95% CI 0.37–0.74, respectively). In conclusion, patients with persistent FN treated with echinocandins had decreased risk of death and adverse events. Both caspofungin and micafungin may be recommended as first-line empirical antifungal therapy in these patients. However, the small number of enrolled patients and the lack of RCTs involving pediatric patients should be considered when using micafungin.